PTH-156 Impact of BSG and BASL Liver Care Bundle Introduction on Clinical Practice: A University Hospital Experience. (17th August 2016) - Shahid, S; Cheung, V; Meghji, H; Rajoriya, N; MacFaul, G
Abstract : Introduction: The National Confidential Enquiry into Patient Outcome and Death for alcohol related liver disease highlighted the need to improve care of patients with decompensated liver disease. BSG and BASL thereafter developed the Liver Care Bundle toolkit to aid provision of evidence-based care within 24 hours of admission. We performed an audit of care delivered to such patients before and after introduction of the Bundle into clinical practice in our hospital. Methods: For the initial audit (August 2014-March 2015), patients presenting with decompensated liver disease were retrospectively identified from ward lists, blood bank data for Human Albumin Solution (HAS), and the endoscopy database. Electronic patient records were reviewed against the toolkit. The results were presented at hospital Grand round alongside presentation of the Liver Care Bundle which was, thereafter, implemented throughout the Trust from July 2015. Re-audit using the same methodology was performed September to December 2015. The significance of impact of the Bundle on clinical practice was evaluated using Fisher's exact test. Results: 45 patients were identified for the first part of the audit. The average length of stay was 11 days. Notes for 20 patients with 25 in-patient episodes were reviewed for the re-audit. Average length of stay was 18 days. Conclusion: The introduction of the Liver Care Bundle at our institution led to improvement in several aspects of care- especially in the management of variceal haemorrhage. Recognition of patients with excess alcohol consumption and use of Pabrinex was improved upon too. There, however, remain clear areas for improvement. Experiences with the Liver Care Bundle should continue to be widely reported in an attempt to standardise and improve in-patient morbidity and mortality in liver disease. Reference: 1 McPherson S, et al. Response to the NCEPOD report: development of a care bundle for patients admitted with decompensated cirrhosis—the first 24 h. Frontline Gastroenterol. 2016 Jan;7 (1):16–23. Epub 2014 Dec 2. Disclosure of Interest: None Declared